3D Character Design for Game "Dungeon Hunter 4" by Gameloft Studio - Duong, Van Dong (Vietnam-Korea University of Information and Communication Technology, 2025)
Graduation thesis of Information Technology - Multimedia Communication; 2020 - 2025